Quality of Methods Reporting in Animal Models of Colitis. Issue 6 (June 2015) - Bramhall, Michael; Flórez-Vargas, Oscar; Stevens, Robert; Brass, Andy; Cruickshank, Sheena
Abstract : Background: Current understanding of the onset of inflammatory bowel diseases relies heavily on data derived from animal models of colitis. However, the omission of information concerning the method used makes the interpretation of studies difficult or impossible. We assessed the current quality of methods reporting in 4 animal models of colitis that are used to inform clinical research into inflammatory bowel disease: dextran sulfate sodium, interleukin-10 −/−, CD45RB high T cell transfer, and 2, 4, 6-trinitrobenzene sulfonic acid (TNBS). Methods: We performed a systematic review based on PRISMA guidelines, using a PubMed search (2000–2014) to obtain publications that used a microarray to describe gene expression in colitic tissue. Methods reporting quality was scored against a checklist of essential and desirable criteria. Results: Fifty-eight articles were identified and included in this review (29 dextran sulfate sodium, 15 interleukin-10 −/−, 5 T cell transfer, and 16 TNBS; some articles use more than 1 colitis model). A mean of 81.7% (SD = ±7.038) of criteria were reported across all models. Only 1 of the 58 articles reported all essential criteria on our checklist. Animal age, gender, housing conditions, and mortality/morbidity were all poorly reported. Conclusions: Failure to include all essential criteria is a cause for concern; this failure can have large impact on the quality and replicability of published colitis experiments. We recommend adoption of our checklist as a requirement for publication to improve the quality, comparability, and standardization of colitis studies and will make interpretation and translation of data to human disease more reliable. Abstract : Article first published online 29 April 2015.Supplemental Digital Content is Available in the Text.